Variable Importance of Macrofaunal Functional Biodiversity for Biogeochemical Cycling in Temperate Coastal Sediments - Braeckman, U; Foshtomi, M. Yazdani; Van Gansbeke, D; Meysman, F; Soetaert, K; Vincx, M; Vanaverbeke, J (Ecosystems (New York), 2014)
Coastal marine systems are currently subject to a variety of anthropogenic and climate-change-induced pressures. An important challenge is to predict how marine sediment communities and benthic biogeochemical cycling will be affected by these ongoing changes. To this end, it is of paramount importance to first better understand the natural variability in coastal benthic biogeochemical cycling and how this is influenced by local environmental conditions and faunal biodiversity. Here, we studied sedimentary biogeochemical cycling at ten coastal stations in the Southern North Sea on a monthly basis from February to October 2011. We explored the spatio-temporal variability in oxygen consumption, dissolved inorganic nitrogen and alkalinity fluxes, and estimated rates of nitrification and denitrification from a mass budget. In a next step, we statistically modeled their relation with environmental variables and structural and functional macrobenthic community characteristics. Our results show that the cohesive, muddy sediments were poor in functional macrobenthic diversity and displayed intermediate oxygen consumption rates, but the highest ammonium effluxes. These muddy sites also showed an elevated alkalinity release from the sediment, which can be explained by the elevated rate of anaerobic processes taking place. Fine sandy sediments were rich in functional macrobenthic diversity and had the maximum oxygen consumption and estimated denitrification rates. Permeable sediments were also poor in macrobenthic functional diversity and showed the lowest oxygen consumption rates and only small fluxes of ammonium and alkalinity. Macrobenthic functional biodiversity as estimated from bioturbation potential appeared a better variable than macrobenthic density in explaining oxygen consumption, ammonium and alkalinity fluxes, and estimated denitrification. However, this importance of functional biodiversity was manifested particularly in fine sandy sediments, to a lesser account in permeable sediments, but not in muddy sediments. The strong relationship between macrobenthic functional biodiversity and biogeochemical cycling in fine sandy sediments implies that a future loss of macrobenthic functional diversity will have important repercussions for benthic ecosystem functioning.